2004
DOI: 10.1161/01.cir.0000146344.49689.bb
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Inflamed Human Endothelial Cells and Influence of Activated Protein C

Abstract: Background-During systemic inflammation, activation of vascular endothelium by proinflammatory cytokines leads to hypotension, microvascular thrombosis, and organ damage. Recent data suggest a link between coagulation and inflammation through the activated protein C (APC) pathway. We studied gene expression profiles in human coronary artery endothelial cells (HCAECs) exposed to proinflammatory stimuli and the influence of APC on expression of candidate genes regulated by these stimuli. Methods and Results-HCAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 37 publications
1
76
0
1
Order By: Relevance
“…Although previous studies have shown that APC administration can attenuate the cytokine perturbation of endothelial cells (38,39), APC appears to be particularly effective in severe sepsis where coagulopathy and thrombin generation is frequent. How can it be explained that thrombin-PAR1 signaling can have proinflammatory effects (8), whereas APC signaling is protective in inflammatory conditions if both thrombin and APC signal through the same receptor?…”
Section: Discussionmentioning
confidence: 90%
“…Although previous studies have shown that APC administration can attenuate the cytokine perturbation of endothelial cells (38,39), APC appears to be particularly effective in severe sepsis where coagulopathy and thrombin generation is frequent. How can it be explained that thrombin-PAR1 signaling can have proinflammatory effects (8), whereas APC signaling is protective in inflammatory conditions if both thrombin and APC signal through the same receptor?…”
Section: Discussionmentioning
confidence: 90%
“…This suggests that in the absence of inflammatory stimuli, APC may not have a significant influence on NFκB activation and that the main effect of this protein seems to be the preservation of cell viability and endothelial barrier function. Anti-apoptotic effects and permeability barrier protection by APC require EPCR binding and PAR1 activation 17,23,24 and these can be induced through both gene expression and post-translational modification of cellular proteins. The finding that genes related to anti-apoptosis are highly up-regulated in our system could explain the inhibition of staurosporineinduced apoptosis by APC on microparticles observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental endotoxininduced inflammation, activated PC inhibits pulmonary vascular injury by inhibiting TNF-␣ release (72) and limits accumulation of activated leukocytes (73). In human EC-based in vitro systems, activated PC modulates expression of genes related to anti-inflammatory and cell survival pathways, including inhibition of NF-B binding to target sites and multiple NF-B-regulated genes, such as cytokines, chemokines, and adhesion molecules (74,75).…”
Section: Ecs In Coagulation and Inflammationmentioning
confidence: 99%